2019
DOI: 10.3390/catal9050448
|View full text |Cite
|
Sign up to set email alerts
|

Complete Hydrodesulfurization of Dibenzothiophene via Direct Desulfurization Pathway over Mesoporous TiO2-Supported NiMo Catalyst Incorporated with Potassium

Abstract: Mesoporous TiO2 containing different potassium content was prepared from potassium titanate by mediating the pH value of the ion exchange, which was used as catalytic support to load NiMo for hydrodesulfurization of dibenzothiophene. The as-prepared samples were characterized by X-ray diffraction, N2 physical adsorption/desorption, temperature-programmed reduction, scanning electron microscope/energy dispersive X-ray mapping analysis, high resolution transmission electron microscopy, and pyridine-adsorbed Four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…The HDS selectivity correlated linearly with the slab length of the MoS 2 phase (TEM), the longer slab length indicated a high ratio of edge/corner and better HDS selectivity, with RhMo/G-Al 2 O 3 presenting the longest slab length [64,77], and the edge sites only catalysed the HDS reaction [78]. The values presented by the current RhMo catalysts (Table 6) exhibit certain benefits and compare well with the other catalysts reported in the literature [79][80][81][82][83][84]. We concluded that the HDS % conversion and desulfurization route was influenced by the catalyst composition, the electronic properties and the HDS reaction conditions.…”
Section: Catalytic Activitysupporting
confidence: 68%
“…The HDS selectivity correlated linearly with the slab length of the MoS 2 phase (TEM), the longer slab length indicated a high ratio of edge/corner and better HDS selectivity, with RhMo/G-Al 2 O 3 presenting the longest slab length [64,77], and the edge sites only catalysed the HDS reaction [78]. The values presented by the current RhMo catalysts (Table 6) exhibit certain benefits and compare well with the other catalysts reported in the literature [79][80][81][82][83][84]. We concluded that the HDS % conversion and desulfurization route was influenced by the catalyst composition, the electronic properties and the HDS reaction conditions.…”
Section: Catalytic Activitysupporting
confidence: 68%
“…The type-H3 hysteresis loop at high relative pressure P/Po, resulting from complete filling and emptying of mesopores by capillary condensation, indicated that all catalysts had slit-shaped mesoporous structures [26,27]. Apart from the NiMo/TiO 2 and NiMo/CaTiO 3 isotherms, other catalysts' isotherms show steep capillary condensation steps, indicating non-uniformity of their mesopores [28]. It could be seen that there was a sudden intersection of the desorption branch with the adsorption branch at a relative pressure of around 0.63 for the NiMo/MgO catalyst, which may be a result of pore blockage due to the different metal cations present in the bulk surfaces, resulting in pores being inaccessible [29,30].…”
Section: Characterization Of Catalystsmentioning
confidence: 99%
“…A similar low-BET surface area of 23.68 m 2 g −1 was reported by [31] for a NiO/TiO 2 catalyst. Li et al [28] also synthesized NiMo-supported TiO 2 catalysts promoted with potassium via the incipient wet impregnation technique and the authors reported a low BET surface area between 39.7 and 45.7 m 2 g −1 for their catalysts. In our previous study [25], NiMo-supported CaTiO 3 catalysts synthesized by the sol-gel method also showed a low BET surface area between 7.7 and 17.4 m 2 g −1 .…”
Section: Characterization Of Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…The crystal structure of various catalysts is studied by XRD. Figure 2a shows five strong diffraction peaks at 25.4 • , 37.8 • , 48.0 • , 53.9 • , and 55.1 • in all catalysts, corresponding to (101), (004), (200), (105), and (211) planes of the anatase phase [28,29], respectively. There are no signals ascribed to other phases of TiO 2 appearing in the XRD spectra.…”
Section: Structural Analysesmentioning
confidence: 99%